The potential role of medicinal mushrooms as prebiotics in aquaculture: A review. (19th January 2022) - Mohan, Kannan; Karthick Rajan, Durairaj; Muralisankar, Thirunavukkarasu; Ramu Ganesan, Abirami; Marimuthu, Kasi; Sathishkumar, Palanivel
Abstract: Aquaculture industry is one of the major food‐producing sectors in the world that provide nutritional food security for mankind. Fish and crustacean farmers are facing various challenges in treating the rapid spread of infectious diseases in recent times. Numerous strategies, including antibiotics, disinfectants, and other antimicrobial agents, have been applied to protect the cultivable aquatic animals from infectious diseases. These applications lead to the development of antimicrobial resistance, toxicity, and the accumulation of antibiotic residues in cells and organelles of the cultivable edible organisms and the environment. The use of naturally derived compounds, polysaccharides, and functional metabolites has gained immense attention among aquaculturists. Mushrooms and their nutraceutical components have been widely used in various sectors, including food, pharmaceutical, poultry, and aquaculture industries, for their non‐toxic and eco‐friendly properties. To date, there are several reports available on edible and medicinal mushrooms as a dietary ingredient for fish and decapod crustacean culture. The mushroom products such as mycelia, stalk, dry powder, polysaccharides, and extracts have been utilized in aquaculture as growth promoters and immunostimulants, improving the digestive enzyme activity, antimicrobials, and improving the health status of cultivable aquatic animals. This present review elucidates the effectiveness of mushrooms and mushroom‐derived compounds as prebiotics in aquaculture. The challenges and future perspectives of mushroom‐derived bioactive molecules have been discussed in this review. Abstract : Medicinal mushrooms and their derivatives as feed supplements to enhance the growth, immunity, gut microbiome and disease resistance of culturable aquatic animals.